Analisis Faktor Yang Mempengaruhi Pemilihan Tempat Menginap di Wonderloft Hostel Jakarta: Analysis of Factors Affecting the Choice of Accommodation at Wonderloft Hostel Jakarta - Ratih Dwi Astuti; Sri Indrayanti; Syalomita Danny (Jurnal Bisnis dan Ekonomi, 2025)
This study aims to analyze the factors influencing the selection of accommodation at Wonderloft Hostel Jakarta. The research employed a qualitative method using structured interviews with 10 guests. The findings indicate that location is the primary consideration (100%), followed by image (90%), promotion (80%), and facilities (70%). The conclusion of this study is that guests’ decisions in choosing Wonderloft Hostel Jakarta are based on a combination of several interrelated factors, with location being the dominant factor.